Potencial imunogênico da Rhipicephalusaquaporina 1 sanguineusde Rhipicephalusem cães(Boophilus)domésticosmicroplus contra o carrapato - Évora, Patricia Martinez [UNESP]; Sanches, Gustavo Seron [UNESP]; Guerrero, Felix David; de León, Adalberto Pérez; Bechara, Gervásio Henrique [UNESP] (FapUNIFESP (SciELO), 2017)
This study evaluated a recombinant aquaporin 1 protein of Rhipicephalus (Boophilus) microplus (RmAQP1) as antigen in a vaccine against R. sanguineus. Five dogs were immunized with RmAQP1 (10 µg) + adjuvant (Montanide) (G1), and five were inoculated with adjuvant only (G2), three times. Twenty-one days after the last immunization, animals of both groups were challenged with R. sanguineus larvae, nymphs and adults, and their biotic potential was compared. Blood samples were collected before each immunization and every 28 days after the last immunization for 10 weeks. Serum antibody titers (IgG) were assessed by ELISA. We observed that: engorgement period of adult females from G1 was 12% shorter than G2; larvae from G1 had 8.7% longer engorgement period than G2 and weighed 7.2% less; nymphs from G1 had 4.5% shorter engorgement period than G2 and weighed 3.6% less; although the antibody titers increased following the second immunization, they rapidly decreased after the third immunization. Results indicated low immunoprotection of RmAQP1 against adult R. sanguineus ticks, and possible efficacy on larvae and nymphs fed on immunized dogs. Further studies should be performed for a full evaluation of the immunoprotection of RmAQP1 against R. sanguineus infestations in dogs.
Immunogenic potential of Rhipicephalus (Boophilus) microplus aquaporin 1 against Rhipicephalus sanguineus in domestic dogs
Keywords: Aquaporin; Domestic dog; Immunity; Rhipicephalus sanguineus; RmAQP1; Ticks